Community-based Investigation of the Risk Factors for Cardiovascular Diseases in Ibadan and suburbs (COMBAT-CVDs): Design and Methods (African Journal of Biomedical Research, 2022)
Africa is gradually becoming the epicentre for the burden of cardiovascular diseases (CVDs) worldwide, and community-based data alluding to the pattern and dynamics of escalating epidemiological thresholds of CVDs among indigenous Africans are limited. This manuscript focuses on the design and methods of Community-based Investigation of the Risk Factors for Cardiovascular Diseases in Ibadan and suburbs (COMBAT-CVDs), an ongoing community-based door-to-door study assessing the profile, burden and dynamics of CVDs risk factors among residents of Ibadan and suburbs. COMBAT-CVDs is a cohort of community-dwelling indigenous Africans, males and females, ≥18years from ten communities in Ibadan, Nigeria. The recruitment of participants for the first wave (W0) started in 2020, covering; questionnaire administration and physical examination. The World Health Organization’s STEPS Instrument for Chronic Disease Risk Factor Surveillance was used for data collection. Data were collected on sociodemographic, socioeconomic, lifestyle-related, history of CVDs, stress, depression and sleep quality. Also, anthropometric and blood pressure measures were conducted by trained personnel using standard operating procedures and instruments. Data collection for the second wave is underway, and the collection of blood and other biological samples for genetic epidemiology is planned, subject to funding availability. For the W0 recruitment, a total of 3638 community-dwelling adults (males – 54.6% and females – 45.4%) participated with a ≥99.7% response rate. The COMBAT-CVDs will likely provide novel data and insightful characterization of CVDs risk factors and ultimately provide evidence for context-specific and culturally relevant interventions for the community-based prevention and management of CVDs among Africans in this setting.